Does central bank independence reflect monetary commitment properly? Methodical considerations - Freytag, Andreas (PSL Quarterly Review, 2012)
Central bank independence (CBI) has attracted much attention in economics and politics in recent years. The concept is based on the political economy literature on monetary policy. In this paper, we argue that CBI is an incomplete approximation to legal monetary commitment. We first discuss the nature and criteria of commitment, then show the shortcomings of the most important indices of CBI before we introduce an alternative measure of legal monetary commitment. This measure is more comprehensive and includes more aspects of commitment than the indices of CBI. A first empirical comparison of this index and a leading CBI index strengthens the argument. JEL Codes: E52, E58